The Spatial Integration of Livestock Markets in Niger. - Fafchamps, M; Gavian, S (Oxford University Press, 1996)
Livestock makes an important contribution to the livelihood of Sahelian farmers and herders and is a source of self-insurance against income shocks. By allocating livestock efficiently over space, spatial market integration should foster a sustainable use of pasture resources. It is also expected to favour the sharing of risk across regions by smoothing idiosyncratic price variations. Using monthly livestock price data from Niger, we show that livestock markets are poorly integrated. Prices are seldom cointegrated, suggesting that large price differentials occasionally persist between adjacent areas for long periods of time. A parity bounds approach indicates that one has to assume high transportation costs and large quality variations to reconcile the data with efficient spatial arbitrage. These results confirm descriptive studies that have emphasised regional segmentation in West African livestock trade.